Nesting site record of the monk parakeet (myiopsitta monachus) in the state of Guerrero, Mexico - Sierra-Morales, Pablo; Almazán-Núñez, R. Carlos (Instituto de Ecología, A.C., 2017)
We recorded for first time the nesting site of the Monk Parakeet (Myiopsitta monachus) to the south of the Chilpancingo city, in the state of Guerrero, Mexico. On 6 August 2015 a nest with two individuals of M. monachus were observed on a Mexican fan palm (Washingtonia robusta). On 21 February 2016, we found a second nest with four individuals on a eucalyptus tree (Eucalyptus spp.). With this data, it is confirmed the breeder status of this invasive species in the state